Expanding the geographic distribution of the freshwater parasite Ceratomyxa (Cnidaria: Myxozoa) with vermiform-type plasmodia. (January 2022) - Zatti, Suellen A.; Adriano, Edson A.; Araújo, Bruno L.; Franzolin, Gustavo N.; Maia, Antônio A.M.
Abstract: Although species of the genus Ceratomyxa Thélohan, 1892 mostly parasitize marine fish around the world, a surprising diversity of the genus has recently been reported from Amazonian freshwater fish. In this study, we report a freshwater Ceratomyxa species parasitizing Hemiodus orthonops (Hemiodontidae) from the Paraná River (La Plata Basin) in a watershed flowing into the southern part of South America, which expands the geographic distribution of this fish parasite in the freshwater resources of the continent. We applied a combination of morphological, small subunit ribosomal DNA (SSU rDNA), and phylogenetic analyses, and vermiform-shaped plasmodia endowed with motility were found swimming in the bile of the fish. The characteristics of the plasmodia and myxospores of the Ceratomyxa species found in the Paraná River resembled those of Ceratomyxa fonsecai, a parasite of the congeneric host Hemiodus unimaculatus from the Tocantins River basin in northern Brazil. Due to the close morphological and morphometric resemblances and the impossibility of genetic comparison, the parasite found in H. orthonops from the Paraná River was designated as Ceratomyxa cf. fonsecai, and the definition of its taxonomic status was left for further study. Maximum likelihood and Bayesian analyses showed Ceratomyxa cf. fonsecai clustering within a well-supported clade, together with other Amazonian freshwater ceratomyxids. The present study suggests that shifts of the complex host/parasite between marine and freshwater environments were facilitated by marine incursions into South America in the Early Miocene. Graphical abstract: Image 1 Highlights: First report of a freshwater Ceratomyxa species from the La Plata Basin. Worm-like plasmodia of Ceratomyxa cf. fonsecai swim freely in the host's bile. The parasite clustered in a subclade of South American freshwater ceratomyxids.